All the lovers in the night : A novel - Kawakami, Mieko (Europa Editions, 2022)
This novel follows Fuyuko Irie, a solitary proofreader in Tokyo, as she struggles with loneliness and self-discovery. Through her relationship with a physics teacher, the story explores themes of connection, light and darkness, and the quiet search for meaning